PERANAN BANTUAN HUKUM TERHADAP MASYARAKAT DALAM MENANGANI PERMASALAHAN HUKUM - Kadek Frediandrika Adnantara (Jurnal Hukum Saraswati, 2024)
The right to legal aid is a human right that conflicts with the law. Legal Aid is a form of access to justice for those affected by legal sanctions. Access to legal aid is also a perversion of equality before the law. Access to legal aid is a human right, especially for underprivileged communities. In this context, Legal Aid centers play an important role in fighting for the rights of the poor and underprivileged, improving their access to the justice system and other legal services.This research will provide knowledge about the role of legal aid centers for the poor and underprivileged. This type of research is normative legal research, answering research questions through empirical support of the Legislation method and analytical methods. The Legal Aid Center has an important role in the application of Law in Court, especially in assisting and/or exercising its authority at the Investigation and Prosecution level, as well as in the Trial Review process until the completion of the case. the case or the judge's final decision